Maternal and Perinatal Outcome in Anemic Pregnancies - Sinha, Kavita; Adhikari, Homnath; Kushwaha, Amrendra; Rimal, Goma (Journal of Nepalgunj Medical College, 2021)
Introduction: Anemia in pregnancy is a public health problem of developing countries and has a significant impact on the health of mother and fetus. It is one of the leading cause responsible for maternal and perinatal morbidity and mortality. Aims: To find out the severity of anemia in pregnancy and its maternal and perinatal outcome. Methods: A prospective randomized case control study undertaken in the Department of Obstetrics and Gynecology, Nepalgunj Medical College, Kolhapur from September 2019 to August 2020. Total of 200 study subjects were enrolled, cases and control were 100 each, with cut off for anemia as 11gm/dl. Results: Out of 100 cases of anemia, 58 were mildly anemic (Hemoglobin: 10-10.9), 23 moderately (7-10) and 21 severely anemic (<7gm/dl). Anemic cases were found to have higher incidence of preterm birth (8%), postpartum hemorrhage (5%), and maternal morbidity (19%) than in non-anemic controls. Adverse fetal outcome in the form of preterm birth (8%), Intrauterine Growth Restriction (14%), Still birth (3%), Early neonatal death (4%), Low birth weight babies (22%), neonatal morbidity (17.5%) was more in anemic group than non-anemic controls. Conclusion: Anemia in pregnancy has adverse effects on the mother and fetus. It is important to diagnose and treat anemia in pregnancy to ensure optimal health of mother and newborn.